Plant Chromosome and Karyotype Analysis Training for High School/MA/Equivalent Teachers in Samarinda and its Surrounding Areas - Oktavianingsih, Linda; Aryani, Retno; Hariani, Nova; Rosadi, Imam; Pratiwi, Anggita Endar; Arif, Muhammad Fauzi (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Increasing biology teachers’ comprehension of the principles of genetics is attainable through the implementation of specialized training sessions focused on chromosome and karyotype analysis. In this training, 21 high school biology teachers from Samarinda and Nears participated in a structured training program encompassing three stages. In the initial phase, participants were provided with materials on the fundamental aspects of genetics. Subsequently, in the second phase, hands-on training was imparted, focusing on acquiring skills in plant chromosome preparation techniques. Lastly, the third stage concentrated on reﬁning skills to construct chromosome karyotyping. Completing all stages was required for participants, followed by submitting evaluation forms for assessment by the committee. The evaluation outcomes revealed that 84.30% of participants regarded the presentation and assistance provided by principal lecturer and assistants as highly commendable. At the same time, the remaining respondents expressed satisfaction with the qualityand adequacy of the training. This comprehensive training eﬀectively equipped participants with specialized chromosome and karyotype analysis skills, and the participants notably absorbed the training materials. The anticipated outcome of enhanced teacher understanding, speciﬁcally in the knowledge of inheritance and chromosome biology, was to stimulate heightened levels of student engagement and learning interest within the biology classroom.